Late disease stage at presentation to an HIV clinic in the era of free antiretroviral therapy in sub-Saharan Africa - Kigozi, Isaac M.; Dobkin, Loren M.; Martin, Jeffrey N.; Geng, Elvin H.; Muyindike, Winnie; Emenyonu, Nneka I.; Bangsberg, David R.; Hahn, Judith A. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2009)
Background: Access to free antiretroviral therapy (ART) in sub-Saharan Africa has been steadily increasing, and the success of large-scale ART programs depends on early initiation of HIV care. However, little is known about the stage at which those infected with HIV present for treatment in sub-Saharan Africa. Methods: We conducted a cross-sectional analysis of initial visits to the Immune Suppression Syndrome Clinic of the Mbarara University Teaching Hospital, including patients who had their initial visit between February 2007 and February 2008 (N=2311). Results: Median age was 33 years (range 16–81). 64% were female. Over one-third (40%) were categorized as late presenters, that is World Health Organization disease stage 3 or 4. Male gender, age 46 to 60 (versus younger), lower education level, being unemployed, living in a household with others, being unmarried, and lack of spousal HIV status disclosure were independently associated with late presentation, while being pregnant, having young children, and consuming alcohol in the prior year were associated with early presentation. Conclusions: Targeted public health interventions to facilitate earlier entry into HIV care are needed, as well as additional study to determine whether late presentation is due to delays in testing versus delays in accessing care
Keywords: Antiretroviral therapy; Access; Sub-Saharan Africa; Late presentation